FORSETI: A visual analysis environment enabling provenance awareness for the accountability of e-autopsy reports - Baoqing Wang; Noboru Adachi; Issei Fujishiro (Visual Informatics, 2022)
Autopsy reports play a pivotal role in forensic science. Medical examiners (MEs) and diagnostic radiologists (DRs) cross-reference autopsy results in the form of autopsy reports, while judicial personnel derive legal documents from final autopsy reports. In our prior study, we presented a visual analysis system called the forensic autopsy system for e-court instruments (FORSETI) with an extended legal medicine markup language (x-LMML) that enables MEs and DRs to author and review e-autopsy reports. In this paper, we present our extended work to incorporate provenance infrastructure with authority management into FORSETI for forensic data accountability, which contains two features. The first is a novel provenance management mechanism that combines the forensic autopsy workflow management system (FAWfMS) and a version control system called lmmlgit for x-LMML files. This management mechanism allows much provenance data on e-autopsy reports and their documented autopsy processes to be individually parsed. The second is provenance-supported immersive analytics, which is intended to ensure that the DRs’ and MEs’ autopsy provenances can be viewed, listed, and analyzed so that a principal ME can author their own report through accountable autopsy referencing in an augmented reality setting. A fictitious case with a synthetic wounded body is used to demonstrate the effectiveness of the provenance-aware FORSETI system in terms of data accountability through the experience of experts in legal medicine.